BACTERIOLOGY OF SPOILAGE OF CANNED PRAWN. - NAMBIAR, V NARAYANAN (Fishery Technology, 2017)
Spoilage characteristics of different types of bacteria isolated from bacteriologically defective cans and processing factory environs were studied by inoculating pure cultures into sterile prawn meat. The pattern of spoilage, namely, production of off odour, bulging of the cans and disintegration ofmeat were observed. Data on spoilage under aerobic as well as anaerobic conditions are presented. Most of the cultures producedsome kind of spoilage, though differences were observed in the extent of spoilage produced by different types of bacteria. Gram positive spore formers were found to be the major spoilers and the extent of spoilage was more with mixed cultures.